Ultrastructural and cell wall modifications during infection of Eucalyptus viminalis roots by a pathogenic Fusarium oxysporum strain - Salerno, María Isabel (2004)
Fusarium species are soil-borne fungal pathogens that produce a variety of disease symptoms when attacking crop plants. The mode of root colonization of Eucalyptus viminalis seedlings by a pathogenic F. oxyporum strain (Foeu1) at the ultrastructural level and changes in cell wall pectin during host pathogen interactions are described. Root systems of E. viminalis plants were inoculated with F. oxysporum in an in vitro model system. Hyphae of F. oxysporum adhered to the outer epidermal cell walls through fibrillar material, and after penetration they spread into the internal tissues. They developed intercellularly and intracellularly in the root cortex and invaded vascular tissues. Papillae were induced, and the host plasma membrane ruptured in colonized cells, causing rapid host tissue and cell damage. Changes in distribution and occurrence of nonesterified and methyl-esterified pectins were evaluated after root colonization by F. oxysporum using two monoclonal antibodies, JIM 5 and JIM 7, respectively. Nonesterified pectin in control roots was mainly localized in the epidermal cell walls and middle lamellae in parenchymal cortex, whereas methyl-esterified pectin accumulated more in primary cell walls of the cortex and phloem. Decreases in immunodetected nonesterified and methyl-esterified pectins were associated with extensive plant tissue degradation after root colonization by the pathogenic fungus.